Design and Evaluation of Chitosan Nanoparticles as Novel Drug Carriers for the Delivery of Donepezil: Chitosan nanoparticles as novel drug carriers donepezil delivery - Dinesh Raja Azalea,; Mazin Mohambed,; Sandra Joji,; C Sankar,; B Mishra, (Iranian Journal of Pharmaceutical Sciences, 2012)
The present study deals with the formulation and evaluation of chitosan nanoparticles containing donepezil hydrochloride for the targeted delivery to the brain. Nanoparticles were prepared by ionic gelation method using sodium tripolyphosphate (TPP) as a cross linking agent followed by sonication. Nanoparticles were obtained in the average size ranging from 116.8 to 227.5 nm. Particle morphology was determined by scanning electron microscopy (SEM). The SEM image showed that each particle unit exhibited a nanostructure. Encapsulation efficiency of nanoparticles ranged between 46.66% and 70.41%. The prepared particles showed good drug-loading capacity. The in vitro release studies showed that after the initial burst, all of the drug-loaded batches provided a continuous and slow release of the drug. Drug released profile was found to be a non-Fickian analomous diffusion, and the drug release was followed by first order kinetics. The drug loaded batches showed a good stability when stored at room temperature for 60 days. FT-IR studies indicated that there was no chemical interaction between the drug and polymer. The present study revealed that ionic gelation technique followed by sonication can be used as an effective tool for preparation of donepezil nanoparticles, which may significantly improve its ability to cross BBB and enter CNS.